Pengembangan Model Pembelajaran Budi Pekerti Berbasis Multikultural - Herimanto Herimanto; Triyanto Triyanto; Musa Pelu (AGASTYA: JURNAL SEJARAH DAN PEMBELAJARANNYA, 2014)
Long-term goal of this study was to character-based learning model can be applied in the implementation of the multicultural character education curriculum in junior high school (SMP) in Surakarta as an effort to prevent a culture of violence in Surakarta. The target of this study is the identification of a model-based development of multicultural learning manners. To achieve these objectives do Research and Development (R & D) gradually for 3 (three) years. This study used a qualitative paradigm, which I pursued in the exploratory method; year to second with the method of exposure, focus groups, workshops, and in-depth interviews; year to III with training methods, test models, evaluation of the test results, the revised and improved model that has been tested, and dissemination of results. development. Concrete measures in the first year were identified: 1) initial ability of teachers to implement character education multicultural education based learning process in implementing character education curriculum. 2) Perception of teachers character education based on learning multicultural education. 3) Perceptions of stakeholders (Department Dikpora / Surakarta City Government, parents / guardians, school character education) to the learning process based multicultural education. 4) Identify the extent of the implementation of character education has been developed through a learning process based on multicultural education, and 5) draft a tentative model of the development of learning-based multicultural character as prevention of the culture of violence in Surakarta. Data collected from other informants, places and events as well as documents / files, or through focus groups, which further analyzed with interactive models.The results obtained in the studies I dart this, namely: (1) The teachers have implemented a character education character-based multicultural learning through discussion methods, simulations, games, community service, observations, as well as the provision of materials in the classroom manners. However, most teachers do not understand the concept of multicultural education, (2) The teachers and stakeholders strongly support the learning plan based multicultural character, given that smells sara violence that often involve the students, (3) learning manners have been implemented with based multicultural through the process of learning, habituation, and modeling. Habituation and modeling performed by all the schools, while the learning process implemented by educators character education, (4) learning manners are still a lot of barriers or obstacles that come dart students, teachers / administrative staff-employees, the environment around the school, funds, facilities and infrastructure, principals, parents, and government policy.